EFFORTS TO REALIZE A HALAL LIFESTYLE IN MADURA THROUGH THE SYNERGY OF ISLAMIC BOARDING SCHOOLS AND THE HALAL CENTER OF UNIVERSITY TRUNOJOYO OF MADURA - Nayu, Moh.; Fahmi, Agung Ali (TRUNOJOYO LAW REVIEW, 2022)
The role of Islamic boarding schools in realizing a halal lifestyle through halal certification as an effort for a better life in the future is a fact. Under certain conditions, Islamic boarding schools can also function as an element that can solve community legal problems. This study is intended to optimize the existence of a halal centre at Trunojoyo University Madura by conducting halal certification through institutional synergy with Islamic boarding schools, which have an essential role in realizing a halal lifestyle in the Madurese community. With empirical legal research methods, it is found that Islamic boarding schools (kiai) have cultural, religious, and legal legitimacy to realize a halal lifestyle in the Madurese community.